Agent Storm : My Life Inside Al Qaeda and the CIA - Storm, Morten; Cruickshank, Paul; Lister, Tim (Journalist) (New York, NY : Atlantic Monthly Press, 2014)
A Danish national-turned-associate of al Qaeda provides an inside look at his decade as a radical Islamist, as well as his ultimate decision to leave the jihadist life and become a double agent for the CIA and British and Danish intelligence.
Morten Storm was an unlikely jihadi. A six-foot-one red-haired Dane, Storm spent his teens in and out of trouble. A book about the Prophet Mohammed prompted his conversion to Islam, and Storm sought purpose in a community of believers. He attended a militant madrasah in Yemen, named his son Osama, and became close friends with Anwar al-Awlaki, the American-born terrorist cleric. But after a decade of jihadi life, he not only repudiated extremism but, in a quest for atonement, became a double agent for the CIA and British and Danish intelligence. Agent Storm takes readers inside the jihadist world like never before, showing the daily life of idealistic men set on mass murder, from dodging drones with al-Qaeda leaders in the Arabian desert to training in extremist gyms in Britain and performing supply drops in Kenya. The book also provides a tantalizing look at his dangerous life undercover, as Storm traveled the world for missions targeting its most dangerous terrorists, and into the world's most powerful spy agencies: their tradecraft, rivalries, and late-night carousing, as well as their ruthless use of a beautiful blonde in an ambitious honey trap. Agent Storm is a captivating real-life thriller.--From publisher description.
Desert road : mid-September 2009 -- Gangs, girls, God : 1976-1997 -- The convert : early 1997-summer 1997 -- Arabia : late summer 1997-summer 1998 -- Londonistan : summer 1998-early 2000 -- Death to America : early 2000-spring 2000 -- Family feuds : summer 2002-spring 2005 -- MI5 comes to Luton : spring-autumn 2005 -- Meeting the Sheikh : late 2005-late summer 2006 -- The fall : late summer 2006-spring 2007 -- Switching sides : spring 2007 -- London calling : spring 2007 -- From Langley with love : summer 2007-early 2008 -- Cocaine and Allah : early 2008 -- Clerical terror : spring-autumn 2008 -- Killing Mr. John : autumn 2008-spring 2009 -- Mujahideen secrets : autumn 2009 -- Anwar's blonde : spring-summer 2010 -- A new cover : summer-winter 2010 -- Target Awlaki : early 2011-summer 2011 -- A long hot summer : July-September 2011 -- Breaking with Big Brother : autumn 2011 -- Back in the ring : late 2011 -- The lion's den : January 2012 -- Operation Amanda : January-May 2012 -- Chinese whispers : May 2012 -- A spy in the cold : 2012-2013.
"First published in Great Britain in 2014 by the Penguin Group"--Title-page verso.
Includes bibliographical references and index.
Keywords: Storm, Morten; Al-Awlaki, Anwar; Storm, Morten; United States. -- Central Intelligence Agency; Qaida (Organization); Intelligence officers -- Denmark -- Biography; War on Terrorism, 2001-2009.; Undercover operations